Effect of hydrophobic groups on the adsorption conformation of modified polycarboxylate superplasticizer investigated by molecular dynamics simulation - Zhao, Hongxia; Wang, Yanwei; Yang, Yong; Shu, Xin; Yan, Han; Ran, Qianping (Applied surface science, 2017)
[Display omitted] •Adsorption conformation of comb-like PCE was studied by all-atom MD simulations.•A comparison is made between vacuum-based and solution-based simulations.•Effects of hydrophobic modifications on adsorption properties are elucidated. All-atom molecular dynamics (MD) simulations were used to study the adsorption conformations of hydrophobically-modified comb-shaped polycarboxylate ether-based (PCE) superplasticizer molecules on a model surface of dicalcium silicate (C2S) in vacuum and in an explicit solution, respectively. Three different hydrophobic modifying groups, namely, the ethyl group, the n-butyl group and the phenyl group, decorated to the backbone, were examined. Comparing the hydrophobically-modified PCEs to the unmodified one, differences were found in the binding energy, the adsorption conformation and the water density at the interface. The interaction between PCE molecules and C2S was weakened in a solution with explicit solvents than that obtained from vacuum-based simulations. The presence of hydrophobic groups lowered the polymer-surface binding energy, decreased the radius of gyration (Rg) of the adsorbed polymer, increased the peak position in the heavy-atom density profiles in the direction perpendicular to the surface, and also caused the adsorbed conformations to be more globular in shape. The parallel and perpendicular components (relative to the surface plane) of the geometric sizes of the adsorbed polymers were calculated, and the results showed that the presence of hydrophobically modifying groups decreased the in-plane radius while increased the adsorption layer thickness compared to the unmodified control. The presence of PCEs perturbed the dense water layer above the C2S surface and lowered the water density. Perturbations to the interfacial water density were found to correlate nicely with the adsorbed conformations of PCEs.